1946
DOI: 10.1172/jci101758
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Loss in Rats With Tourniquet Shock 1

Abstract: Release of a high unilateral tourniquet producing complete interruption of blood flow to a hind limb of the rat for about 5 hours almost invariably results in fatal shock. The development of shock is accompanied by progressive edema of the limb. The main object of the following experiments was to determine the magnitude and the rapidity of the fluid loss in the injured extremity. METHODSAdult white male rats weighing about 150 to 300 grams were used. These were anesthetized with sodium pentobarbital, given int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1956
1956
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The hemodynamic changes observed during acute pancreatitis, i.e., arterial hypotension and reduction of cardiac output, are attributed to hypovolemia due to massive fluid loss into the tissues and release of vasoactive substances and inflammatory mediators [16,29,30]. In the tourniquet shock model, hypotension is also induced by fluid sequestration in combination with release of vasoactive substances and inflammatory mediators [16,18]. We demonstrated that arterial hypotension due to tourniquet shock enhances progressive capillary perfusion failure during…”
Section: Arterial Hypotension and Acute Pancreatitis (Group Isovolemimentioning
confidence: 99%
See 1 more Smart Citation
“…The hemodynamic changes observed during acute pancreatitis, i.e., arterial hypotension and reduction of cardiac output, are attributed to hypovolemia due to massive fluid loss into the tissues and release of vasoactive substances and inflammatory mediators [16,29,30]. In the tourniquet shock model, hypotension is also induced by fluid sequestration in combination with release of vasoactive substances and inflammatory mediators [16,18]. We demonstrated that arterial hypotension due to tourniquet shock enhances progressive capillary perfusion failure during…”
Section: Arterial Hypotension and Acute Pancreatitis (Group Isovolemimentioning
confidence: 99%
“…With fixed tourniquets, preparation was finished and baseline measurements were taken. Release of the tourniquets after 4.0 hr, simultaneous with induction of pancreatitis, was accompanied with an immediate fall in arterial blood pressure (65 { 4 mm Hg 5 min after release) due to massive fluid sequestration and liberation of inflammatory mediators [16,18]. Pancreatitis was induced in all animals at 4.0 hr after start of preparation, except in animals allocated to group HYP.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial pressure in rats with fatal tourniquet shock shows 3 main phases: (1) an abrupt fall immediately after tourniquet release, ( 2 ) sustained hypotension within a relatively nlarrow range during most of the shock state, and ( 3 ) a terminal more or less rapid decline associated with death. Only in the terminal period does profound hypotension intervene, with levels below 40 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Wir nehmen an, dab die ErhShung des osmotisehen Gewebsdruckes ein entscheidender Faktor bei der (~demgenese ist, was durch unsere Untersuchungen an Ratten und Hunden belegt wurde [20,25]. B. nach Embolektomien, nicht hinreichend erkl/~ren, t{ier wird nur ein kleines operationsbedingtes Gewebstraum~ gesetzt, das nicht mit dem AusmaB des C)dems korrelierbar ist.…”
Section: Diskussionunclassified